Paclitaxel, interferons and functional reprogramming of tumor-associated macrophages in optimized chemo-immunotherapy - Pawel Kalinski; Kathleen M Kokolus; Shipra Gandhi (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibition (ICI) targeting programmed cell death protein-1 (PD1) prevents the elimination of activated cytotoxic T lymphocytes (CTLs) by programmed death-ligand 1/2-expressing cancer and myeloid cells in the tumor microenvironment (TME). ICI has shown its effectiveness in many solid tumors, but it lacks activity against “cold” tumors which lack CTL infiltration, including most of the colon, prostate, lung and breast cancers. Metastatic triple-negative breast cancer (TNBC) responds to PD-1 blockade only in 5–20% cases. Chemotherapy has been shown to have a PD1-sensitizing effect in a fraction of patients with TNBC but the underlying mechanism and the reasoning behind its limitation to only a subset of patients are unknown. Recent data demonstrate the key roles played by paclitaxel-driven Toll-like receptor 4 (TLR4) signaling and the resulting activation of type-1 and type-2 interferon pathways in tumor-associated macrophages, resulting in local M2 to M1 transition and enhanced tumor antigen cross-presentation, in the paclitaxel-driven sensitization of “cold” tumors to ICI. These data and the known ability of the TLR4-activated MyD88-NFκB pathway to mobilize both antitumor and tumor-promoting events in the TME provide new tools to enhance the efficacy of chemo-immunotherapy for metastatic, and potentially early, TNBC and other taxane-sensitive cancers.